Sydney Popular Financial Report 2021-2022 - Andrea Sapei; Yasaman Mokhtari Azad; Yuhang Zheng (European Journal of Volunteering and Community-Based Projects)
This report provides an overview of the City of Sydney for the fiscal year 2021-22. It covers key topics such as the city's recovery from the COVID-19 pandemic, its demographic data, key policies, and financial statements. - A letter from the Lord Mayor, Clover Moore, talks about the challenges and recovery efforts in the city due to the COVID-19 pandemic. Support for the community, especially international students, has been continuous. - Sydney, the capital of New South Wales, stands as the most populous city in Australia and is well known for its diverse culture and high quality of life. The General Data section details the city's demographic data, including gender distribution, population size, and age distribution. It also houses details about community participation in the labor force. - Major policies in Sydney are directed at objectives such as environmental sustainability, housing affordability, and addressing inequality. These policies aim to improve the quality of life for all residents. - The report also presents the financial statements for the fiscal year ended on June 30th 2022, providing insights into the city's financial position. - The methodological notes section explains the standards used for preparing the financial statements and the report, as well as the division of work among the team.